PanM, an Acetyl-Coenzyme A Sensor Required for Maturation of l-Aspartate Decarboxylase (PanD) - Tara N. Stuecker (American Society for Microbiology, 2012)
ABSTRACT Coenzyme A (CoA) is essential for cellular chemistry in all forms of life. The pantothenate moiety of CoA is generated from the condensation of pantoate and β-alanine. β-Alanine is formed by decarboxylation of l-aspartate catalyzed by PanD, a pyruvoyl enzyme that is synthesized by the cell as an inactive precursor (pro-PanD). Maturation of pro-PanD into PanD occurs via a self-cleavage event at residue Ser25, which forms the catalytic pyruvoyl moiety. We recently reported that Salmonella enterica PanM was necessary for pro-PanD maturation, both in vitro and in vivo. Notably, PanM is annotated as a Gcn5-like N-acetyltransferase (GNAT), which suggested that lysine acetylation might be part of the mechanism of maturation. Here we show that PanM lacks acetyltransferase activity and that acetyl-CoA stimulates its activity. Results of experiments with nonhydrolyzable ethyl-CoA and genetically encoded acetyl-lysine-containing PanD support the conclusion that PanM-dependent pro-PanD maturation does not involve an acetyl transfer event. We also show that CoA binding to PanM is needed for in vivo activity and that disruption of CoA binding prevents PanM from interacting with PanD. We conclude that PanM is a GNAT homologue that lost its acetyltransferase activity and evolved a new function as an acetyl-CoA sensor that can trigger the maturation of pro-PanD. IMPORTANCE Nε-lysine acetylation is increasingly being recognized as a widespread and important form of posttranslational regulation in bacteria. The acetyltransferases that catalyze these reactions are poorly characterized in bacteria. Based on annotation, most bacterial genomes contain several acetyltransferases, but the physiological roles of only a handful have been determined. Notably, a subset of putative acetyltransferases lack residues that are critical for activity in most biochemically characterized acetyltransferases. We show that one such putative acetyltransferase, PanM (formerly YhhK), lacks acetyltransferase activity but functions instead as an acetyl-coenzyme A (CoA) sensor. This work establishes the possibility that, like PanM, other putative acetyltransferases may have evolved new functions while retaining the ability to sense acetyl-CoA.